The Use of Biofertilizers Increased Plant Growth with No Trade-Off Effect on GreenHouse Gas Emission - Abdul Hadi; Udiantoro .; Hasrul Satria Nur; Muhlis , (Center for Journal Management and Publication, 2017)
Several experiments have been carried out to elucidate the reduction in greenhouse gas emissions as effect of replacement of chemical fertilizer by biofertilizers on alluvial soils in Indonesia.Â Biofertilizers â€œBiotaraâ€ and â€œBiosureâ€ were applied along with NPK fertilizer on alluvial soil cultivated with rice.Â Emissions of nitrous oxide (N2O), methane (CH4) and carbon dioxide (CO2) were monitored in biweekly basis up to the maximum vegetative growth of the rice plant. Oil palm empty fruit bunch (OP EFB) as well as grasses were composted with Bacillus brevis and Bacillus megaterium as activator. The composts were incorporated into alluvial soils cultivated to oil palm and the emissions of N2O, CH4 and CO2 were monitored in biweekly basis. The results showed that biofertilizer â€œBiotaraâ€ or â€œBiosureâ€ combined with NPK fertilizer (Â¾ recommendation dose) could increase paddy growth with no significant effect on N2O, CH4 and CO2 emissions.Â The emissions of N2O,Â CH4 and CO2 exhibited seasonal changes as affected by inclusion of either OP EFB and weed compost along with NPK fertilizer.Â Global warming potentials of each treatment for NPK, OP EFB compost and weed compost were 5.6, -5.2 and -4.9 ton CO2equ m-2 year-1, respectively. It could be concluded that the replacements of synthetic fertilizer with biofertilizer or compost did not have negative impact on the environment which could be promoted.